The grumpy bunny joins the team - Korman, Justine; McQueen, Lucinda ([Mahwah, N.J.?] : WhistleStop, 1998)
Hopper the grumpy bunny has to help coach the school baseball team. But Hopper doesn't like baseball--not one bit! And three of his players are pretty hopeless. Can Hopper find a way to turn them into winners?
Keywords: Rabbits -- Juvenile fiction; Baseball teams -- Juvenile fiction